SARS-CoV-2 S assembly into virions facilitated by host ERM proteins - Jiaming Wang; Wanbo Tai; Zhaoyang Wang; Wenxin Dai; Mingrui Yang; Jiajian Guo; Pengfei He; Yanan Nan; Tianyu Li; Shuqi Zhou; Dongxiao Cui; Yiqun Li; et al. (Proceedings of the National Academy of Sciences, 2026)
The host cell cytoskeleton plays a critical role in the SARS-CoV-2 life cycle, though the underlying mechanisms remain poorly understood. This study investigates the interaction between the SARS-CoV-2 spike (S) protein and the cytoskeleton-associated ezrin-radixin-moesin (ERM) proteins through biochemical and structural characterization. A previously unidentified ERM-binding motif on the SARS-CoV-2 S protein is identified, revealing that S-ERM interactions are specifically conserved among highly pathogenic coronaviruses, including SARS-CoV, MERS-CoV, and SARS-CoV-2. Functionally, these interactions facilitate S packaging into virions by directing it to assembly sites, utilizing ERM’s affinity for negatively curved membranes, akin to its role in cell surface protrusions. Silencing ERM expression significantly reduces SARS-CoV-2 titer, highlighting its essential role in viral propagation. Additionally, leveraging the established role of COPI-mediated trafficking in S localization, a compound is developed to disrupt S-COPI binding, promoting S secretion to the cell surface and effectively reducing viral titers. Our findings revealed a critical host–pathogen interaction that drives S incorporation into virions and identified ERM proteins as key facilitators of coronavirus assembly. Furthermore, our study suggests an antiviral strategy by targeting the S-COPI trafficking pathway. These insights advanced our understanding of coronavirus–host interactions and provided a potential therapeutic approach against SARS-CoV-2 and other highly pathogenic coronaviruses.